Effect of Intravenous Aminocaproid Acid on Blood Loss and Transfusion Requirements After Bilateral Varus Rotational Osteotomy: A Double-blind, Placebo-controlled Randomized Trial. Issue 6 (July 2020) - Swarup, Ishaan; Nguyen, Joseph; Edmonds, Chris; Dodwell, Emily; Scher, David
Abstract : Background: ε-Aminocaproic acid (EACA) is an antifibrinolytic agent that has been shown to decrease blood loss and transfusion requirements in several populations undergoing various surgical procedures. However, the efficacy of EACA has not been assessed in pediatric patients with cerebral palsy undergoing bilateral varus rotational femoral osteotomies. The purpose of this study was to assess the efficacy of intravenous EACA in reducing calculated intraoperative blood loss and transfusions in this population. Methods: Patients aged 18 years or younger were eligible. Patients were randomized to receive EACA or placebo (saline), and randomization was stratified based on sex and whether or not additional soft tissue or osseous procedures were performed. On the basis of retrospective data, the calculated sample size was 12 patients per arm to detect a difference of 250-mL blood loss. The primary outcome was calculated intraoperative blood loss. Secondary outcomes included transfusion requirements, 24-hour drain output, length of stay, and incidence of complications. Results: The mean age of patients in this study was 8 years (SD: 2.4 y). There were no differences in age, sex, height, weight, type of anesthesia, operative time, and associated procedures between the EACA and placebo groups ( P >0.05). Preoperative hematocrit was lower in the EACA group (37.1 vs. 40.0, P =0.04). Calculated intraoperative blood loss was 536 mL in the EACA group and 628 mL in the placebo group ( P =0.45). Transfusions were required in 62% of patients in the EACA group and 67% of patients in the placebo group ( P =0.68). Total 24-hour drain output was 72.5 mL in the EACA group and 103.3 mL in the placebo group ( P =0.37). Length of stay was similar between both groups, and there were no drug or placebo-related complications in either group. Conclusions: There was no difference in blood loss or transfusion requirements associated with EACA compared with placebo; however, this study is underpowered to detect smaller differences in blood loss. Additional studies with larger sample sizes are needed to confirm these findings and further elucidate the indications for antifibrinolytic agents in pediatric patients. Level of Evidence: Level I.